Augmentation de la biomasse en circulation au travers de couverts et mélanges de couverts végétaux : Expérience française - Thomas F. (Troisièmes rencontres méditerranéennes du semis direct, 2006)
Several plant covers have been tested and assessed, through the network of Breton farmers (BASE) and of other sectors in the country. This approach has helped us devising the plant mixtures or the synergy of these associations which permit the production of more biomass in record time (between 5 and 7 t/ha of dry matter in only 2.5 to 3 months). In retrospect, and in addition to soil cover, we have noted this approach enhances nutritional balance in crops, providing an excellent control of weeds. Likewise, these cover mixtures are prepared for most plants that are sensitive to frost which, together with rolling (French 'Rolo faca'), allow the destruction without having to use herbicides systematically. If the key to success lies on optimal and adapted implementation of intercrop cover, it is essential to develop a new rotation approach in parallel.
3. Mediterranean Meeting on no Tillage, 2006/03/23-25, Zaragoza (Spain)